PENERAPAN BLENDED-PROBLEM BASED LEARNING DALAM PEMBELAJARAN BIOLOGI - Samuel Agus Triyanto; Herawati Susilo; Fatchur Rohman (Graduate School of Universitas Negeri Malang, 2016)
Biology 21st century is the integration and reintegration of sub disciplines of biology, and the integration with other disciplines to address social problems. This research aims to determine the application of Blended-Problem Based Learning, student activities, and student response in learning of biology. This research is a survey with a qualitative descriptive approach. The results showed that the positive of student activities in learning is satisfactory, while the student response to learning is good. Based on the findings, it was concluded that the Blended-Problem Based Learning can be applied and was accepted as a model in learning.Biologi abad 21 merupakan integrasi dan mengintegrasikan kembali sub disiplin ilmu biologi, serta integrasi biologi dengan disiplin ilmu lain untuk mengatasi permasalahan sosial. Penelitian ini bertujuan untuk mengetahui penerapan Blended-Problem Based Learning, aktivitas belajar, dan respon siswa dalam pembelajaran biologi. Penelitian ini merupakan penelitian survei dengan pendekatan deskriptif kualitatif. Data hasil penelitian menunjukkan bahwa aktivitas positif siswa dalam pembelajaran memuaskan, sedangkan respon siswa baik terhadap pembelajaran. Berdasarkan hasil penelitian, disimpulkan bahwa Blended-Problem Based Learning dapat diterapkan dan diterima sebagai model dalam pembelajaran.